Stereotactic radiosurgery combined with anlotinib for limited brain metastases with perilesional edema in non‐small cell lung cancer: Rvision‐001 study protocol - Yuxia Wang; Xin Wang; Yun Guan; Yongchun Song; Hongqing Zhuang; Enmin Wang (Thoracic Cancer)
Introduction About 50% of patients with non‐small cell lung cancers (NSCLC) are diagnosed with brain metastases during treatment, and stereotactic radiosurgery (SRS) is an important treatment for brain oligometastasis. Some patients with brain metastases have cerebral edema before treatment, and radiation therapy may also cause, or aggravate brain edema. Vascular endothelial growth factor (VEGF) promotes angiogenesis and increase vascular permeability, and previous studies have shown that anti‐VEGF treatment can reduce brain edema. We hypothesized that anlotinib hydrochloride can reduce perilesional edema around brain metastases, create conditions for subsequent SRS, increase local control rate and improve patient prognosis. Methods From one week before stereotactic radiosurgery, patients begin to receive anlotinib once a day (12 mg) from day 1–14 of a 21 day cycle, with two cycles in total. Brain magnetic resonance imaging (MRI) scan is taken before treatment, one week and one month after medication. A total of 50 patients will be included in this study. The primary endpoint is the Edema Index, and the secondary endpoints are intracranial objective response rate (iORR), intracranial progression‐free survival (iPFS), objective response rate (ORR), disease control rate (DCR), progression‐free survival (PFS), overall survival (OS), safety, and the rate of SRS after anlotinib treatment. Discussion This study is a multicenter, prospective, single‐arm, phase II clinical study, and explores the efficacy and tolerability of SRS with anlotinib in NSCLC patients with limited brain metastases. The aim of the study is to provide new treatment options for NSCLC patients with brain metastases.